Pengenalan website kampung sebagai media digitalisasi dan promosi potensi lokal Kampung Kwau, Kabupaten Manokwari: Introducing the village website as a digital platform for digitalization and promotion of local potential in Kwau Village, Manokwari Regency - Andreas Sumendap; Dedi I. Inan; Josua J. A. Limbong; Ratna Juita; Christian D. Suhendra; Lion F. Marini; Lorna Y. Baisa; Lilis Indrayani; Julius P. P. Naibaho; Marlinda Sanglise; Alex De Kweldju (Fakultas Peternakan Universitas Papua, 2026)
ABSTRACT Digitalization of rural communities is a strategic approach to promoting local potential and empowering communities through the utilization of information technology. Kwau Village, located in Mokwam District, Manokwari Regency, possesses considerable tourism, cultural, and local resource potential that has not been optimally promoted through digital media. This community service program aimed to introduce a village website as a platform for digitalization and promotion of local potential while enhancing community capacity in website management. A participatory approach was employed through observation, interviews, socialization, training, mentoring, and qualitative evaluation. The socialization activities were attended by 37 participants, while 25 participants actively took part in website development and management training. Four village youths were trained as website administrators to support the sustainability of website management. The results showed that participants were able to understand the functions and utilization of the website as a medium for information dissemination and local promotion. Furthermore, a village website was successfully developed containing 13 articles, 11 photographs, and 3 videos presenting village profiles, tourism attractions, cultural heritage, and local products. Although challenges related to limited technological infrastructure and internet access remain, the program demonstrates that a participatory approach combined with simple technological solutions can effectively support village digitalization and expand the promotion of local potential in a sustainable manner. Keywords: Digitalization; Kwau Village; Local Potential; Promotion; Website ABSTRAK Digitalisasi kampung merupakan salah satu upaya strategis untuk mendukung promosi potensi lokal dan pemberdayaan masyarakat melalui pemanfaatan teknologi informasi. Kampung Kwau, Distrik Mokwam, Kabupaten Manokwari, memiliki potensi wisata, budaya, dan sumber daya lokal yang belum dipromosikan secara optimal melalui media digital. Kegiatan pengabdian kepada masyarakat ini bertujuan memperkenalkan website kampung sebagai media digitalisasi dan promosi potensi lokal serta meningkatkan kapasitas masyarakat dalam pengelolaannya. Metode yang digunakan adalah pendekatan partisipatif melalui observasi, wawancara, sosialisasi, pelatihan, pendampingan, dan evaluasi kualitatif. Kegiatan sosialisasi diikuti oleh 37 peserta, sedangkan 25 peserta terlibat dalam pelatihan pembuatan dan pengelolaan website. Sebanyak 4 orang pemuda kampung dilatih sebagai admin website untuk mendukung keberlanjutan pengelolaan sistem. Hasil kegiatan menunjukkan bahwa peserta mampu memahami fungsi dan penggunaan website sebagai media informasi dan promosi kampung. Selain itu, berhasil dikembangkan website kampung yang memuat 13 artikel, 11 foto, dan 3 video yang menampilkan profil kampung, potensi wisata, budaya, serta produk lokal. Meskipun masih terdapat kendala berupa keterbatasan infrastruktur teknologi dan akses internet, program ini menunjukkan bahwa pendekatan partisipatif dan pemanfaatan teknologi sederhana dapat mendukung digitalisasi kampung serta memperluas promosi potensi lokal secara berkelanjutan. Kata kunci: Digitalisasi; Kampung Kwau; Potensi Lokal; Promosi; Website